Body Image, Body Shamming, Self- The Relationship Between Body Image and Body Shaming on Self-Esteem Among Final Year Students: The Relationship Between Body Image and Body Shaming on Self-Esteem Among Final Year Students - Fadhillah, Ummul (At-Taujih: Jurnal Bimbingan dan Konseling Islam, 2025)
Body shamming  can cause a decrease in self- confidence in students, because body shamming  is an act of bullying carried out through negative comments on other people`s physical appearance. body shamming  can have causing depression, eating disorders, and explain the relationship between body image  and  body shamming  in final year students. this research uses a quantitative approach using correlational methods. the total sample was 110 final year students. sampling was carried out using the purposive sampling method. the measuring tool in this research is the body image  scale which is prepared based on the aspects proposed by cans and pruzinsky, the  body shamming  scale is prepared based on the aspects presented by duarte et al and the self- confidence scale is prepared based on the aspects stated by duarte et al. The results of the research show that the significance value of the  body image  variable on the self- confidence variable is 0,000< 0,05, so the variables are said to be correlation between and self- confidence is  0,025, so the correlation between variables is said tobe strong. meanwhile, the  body shamming  variable on self-confidence is 0,000> 0,05, do the variable is said to be uncorrelated. the correlation level between body shamming  variable and self-confidence is 0,774, so the variable is said to be weak